Single Mo atoms paired with neighbouring Ti atoms catalytically decompose ammonium bisulfate formed in low-temperature SCR. Issue 11 (15th November 2021) - Chen, Junxiao; Fang, Xue; Ren, Zhouhong; Qu, Weiye; Hu, Xiaolei; Ma, Zhen; Chen, Liwei; Liu, Xi; Chen, Yaxin; Tang, Xingfu
Abstract : We developed a TiO2 -supported single-atom Mo catalyst (Mo1 /TiO2 ) where single Mo atoms paired with the neighboring surface Ti atoms function as Mo–Ti acid–base dual sites, realizing the decomposition of ABS at ∼225 °C. Abstract : Selective catalytic reduction (SCR) of NO x with NH3 has been widely used for NO x emission control, but commercial catalysts inevitably suffer severe deactivation in SO2 -containing stack gases at low temperatures because the ammonium bisulfate (NH4 HSO4, ABS) formed in SCR blocks the surface active sites. We resolve this issue by developing a TiO2 -supported single-atom Mo catalyst (Mo1 /TiO2 ) that decomposes ABS at ∼225 °C, far lower than the dew point of ABS (∼260 °C). Single Mo atoms paired with the neighboring surface Ti atoms function as Mo–Ti acid–base dual sites, which respectively adsorb the NH4 + and HSO4 − of ABS. After the oxidation of NH4 + by surface lattice oxygen on the Mo sites, electrons left behind on the dual sites are localized around the Fermi level, which allows them to transfer to the adsorbed HSO4 − on the Ti sites, thus releasing SO2 at low temperatures. The Mo1 /TiO2 catalyst with Mo–Ti acid–base dual sites enables the decomposition of ABS at low temperatures, and thus this work provides a way to effectively control NO x emission particularly from industrial boilers.